ROS-based nanomedicines for anti-inflammatory therapies - Mathieu Repellin; Hanäé Guerin; Giuseppina Catania; Giovanna Lollo (Bioscientifica, 2024)
Reactive oxygen species (ROS) are important signaling molecules that play key roles in the progression of inflammatory disorders. Owing to a mismatch of the antioxidant level to balance the overproduction of ROS, the induced chronic inflammation can lead to several type of diseases such as cancer, inflammatory bowel disease, atherosclerosis, diabetes or neurodegenerative disorders. Over the last years, nanomedicine has shown tremendous promise in ROS-regulating approaches. The development of advanced redox-active nanomaterials opened the range of possibilities to anti-inflammatory therapies, with the production of ROS-responsive nanosystems enabling targeted drug delivery or with the manufacture of ROS-scavenging nanomaterials reducing ROS excess levels. This review summarizes the latest developments and novel designs of ROS-based nanomedicines and discusses their therapeutical strategies and applications.